1922
DOI: 10.1128/jb.7.2.183-230.1922
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection Studies the Effects of Temperature and Hydrogen Ion Concentration Upon the Viability of Bact. Coli and Bact. Typhosum in Water

Abstract: Exposure to extremes of temperature and of hydrogen ion concentration produces an accelerated death rate of bacteria. These aTe typical conditions of ordinary disinfecting procedures. Temperatures and hydrogen ion concentrations in the zones between those which are favorable and those which are distinctly lethal may be expected to produce an adaptation in the organisms or a comparatively slow death rate, knowledge of which may reveal the conduct of bacteria under moderately unfavorable conditions in nature, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1923
1923
1957
1957

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Not all types of bacteria die rapidly when placed in water or saline. The coli-aerogenes group and the morphologically and biochemically related Salmonella and Proteus groups can survive, in undiminished numbers, for many hours and even days in water (Cohen, 1922;Osborne, 1955, 1956). But as has been indicated, many bacteria, including aerobic sporeformers, pseudomonads, and other common inhabitants of foods die very rapidly, within minutes, when suspended in water or saline.…”
Section: Discussionmentioning
confidence: 99%
“…Not all types of bacteria die rapidly when placed in water or saline. The coli-aerogenes group and the morphologically and biochemically related Salmonella and Proteus groups can survive, in undiminished numbers, for many hours and even days in water (Cohen, 1922;Osborne, 1955, 1956). But as has been indicated, many bacteria, including aerobic sporeformers, pseudomonads, and other common inhabitants of foods die very rapidly, within minutes, when suspended in water or saline.…”
Section: Discussionmentioning
confidence: 99%
“…It is typical of these reactions, such as the killing of bacteria by disinfectants (12,13,14), the limitation of the duration of life of fruit flies by untoward conditions of environment (15), or the hemolysis of erythrocytes by specific antibodies, or by ultra violet light (16) that the middle portion of the experimental curve may be reproduced mathematically by the equation that also describes the course of monomolecular chemical reactions. The formula tempts one to speculate, by analogy, on the nature of the fundamental biological reactions involved.…”
Section: Discussionmentioning
confidence: 99%
“…Others working with Staphylococcus aureus have experienced this day-to-day variation in the same culture, and Cohen (1922) found a probable error of 2 or 3 per cent under the most ideal conditions, and as high as 10 per cent in most of his work. Smyth (1934) published the results of his 'detailed experiments on factors influencing the phenol resistance of Staphylococcus aureus, and concluded that any small deviation, such as concentration of disinfectant and of cells, the temperature a t which the disinfection test is conducted, the age of the culture and even a 1' difference in the incubator temperature, will cause variations.…”
Section: -80mentioning
confidence: 92%